2019
DOI: 10.5194/esurf-7-439-2019
|View full text |Cite
|
Sign up to set email alerts
|

Testing a failure surface prediction and deposit reconstruction method for a landslide cluster that occurred during Typhoon Talas (Japan)

Abstract: Abstract. Reconstructions of failure surfaces (prior to potential landslides or after their release), landslide deposits, or other palaeotopographic features are important for hazard and erosion assessment. The volumes involved in landslide and failure surfaces constrain the propagation of a landslide, and knowledge of the past topography helps us to understand these hazards. Some methods exist to characterise landslide geometry, but these methods usually require monitoring information. This study tries to ass… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…For approximating the 3D failure surface, Jaboyedoff et al (2004) and Jaboyedoff et al (2009) proposed the Sloping Local Base Level (SLBL) method to construct a curved surface, of which the second derivative along the down-slope direction remains constant. The SLBL technique has been tested against landslides triggered by Typhoon Talas in Japan, where reasonable agreements (±35%) were achieved (Jaboyedoff et al, 2019). For studying the 3D stability of stratovolcano edifice, Reid et al (2000) and Reid et al (2001) suggested a spherical failure surface for analyzing the slope stability by using the LEM without considering the internal/local structures.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…For approximating the 3D failure surface, Jaboyedoff et al (2004) and Jaboyedoff et al (2009) proposed the Sloping Local Base Level (SLBL) method to construct a curved surface, of which the second derivative along the down-slope direction remains constant. The SLBL technique has been tested against landslides triggered by Typhoon Talas in Japan, where reasonable agreements (±35%) were achieved (Jaboyedoff et al, 2019). For studying the 3D stability of stratovolcano edifice, Reid et al (2000) and Reid et al (2001) suggested a spherical failure surface for analyzing the slope stability by using the LEM without considering the internal/local structures.…”
Section: Introductionmentioning
confidence: 94%
“…However, the complex composition, spatial geological structure, and hydrological variations lead the determination of a precise failure surface on the natural slopes in mountain areas to a highly challenging task, especially when the field data are incomplete. Hence, the determination/prediction of a landslide failure surface and estimation of the associated volume of released mass are with a high degree of uncertainty (e.g., Jaboyedoff et al, 2019;Yeh et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The volume balance of pre and post-failure state of the slope (considering a bulking factor of 15%, i.e., volume expansion during collapse; cf. Jaboyedoff et al [64]) was established in its 3D geomodel. Here, a 2D section was extracted from the latter and used as input profile in UDEC.…”
Section: Modelled Slope Morphologies and Rock Structuresmentioning
confidence: 99%
“…Both can be determined from the surface envelope separating the stable and unstable materials, and corresponding to potential rupture surfaces. This envelope can be deduced from the extent of the landslide on the topography and relative simple geometric considerations, provided the subsurface is homogeneous (Jaboyedoff et al, 2019(Jaboyedoff et al, , 2020. The determination of the landslide extent is a problem by itself: it can be inferred, for instance, from field observations or records of surface displacements (e.g.…”
mentioning
confidence: 99%
“…InSAR acquisition for displacement measurements does not yield conclusive results in densely vegetated areas). Besides, in volcanic context, simple geometric considerations linking the rupture surface to the extent of the unstable mass may not be applicable either (Jaboyedoff et al, 2019(Jaboyedoff et al, , 2020: the volcanic formations below the surface are often not homogeneous and can display complex geometries. In these conditions where relatively few data are available but stakes require a quantified hazard assessment, how can we estimate the surface envelope of an unstable mass, from which the unstable volume can be quantified?…”
mentioning
confidence: 99%